THE DEVELOPMENT OF DIGITAL ILLUSTRATION TO HELP STUDENT’S COMPREHENSION IN READING NARRATIVE TEXT: A RESEARCH AND DEVELOPMENT - Diana Puspasari; Teguh Kasprabowo (Dinamika Bahasa dan Budaya, 2022)
This study aims to know the lecturer’s and student’s perspectives on the use of digital illustrations or digital storybooks, this study also aims to develop a digital picture book for learning to read narrative text. This study is about research and development or also known as R&D, which produces products that help students’ comprehension in reading narrative text. The data was taken from the questionnaire and open-ended interviews that have been shared by the respondents. According to Borg and Gall (1983), R&D is “The process used to develop and validate educational products”. The results of this research not only develop existing products but also on finding knowledge, middle ground, or answers to existing problems. This study found that the respondents like story books with pictures and colors, they also assume that illustration can help their understanding of reading narrative text, and they think that the use of the visual learning method is a good method and not monotonous to teach and learn especially in English learning, they also said that this product can be developed further, and for the last, they think that learning media via easy-to-access link is a good medium for learning. Keywords: Digital illustration, Narrative text, Research and development, Visual, Learning, Media